The Dynamics and Role of Sufism in Turkish Politics and Society - Darmaiza Darmaiza; Meirison Meirison; Ayu Rustriana Rusli; Qasim Muhammadi (Teosofia: Indonesian Journal of Islamic Mysticism, 2022)
Sufism is widespread in Turkey, and most Turkish people sympathise with the Sufis even if they do not adhere to particular Sufi orders. Sufism has been rooted in Turkish society throughout history and has experienced ups and downs. This article is a literature study that used a qualitative approach and descriptive analysis. Data were collected from documents, literature, and journals. This study found that Sufism was not entirely swept up by secularisation, particularly in rural areas. Even in urban areas, many still adhere to Islamic traditions, including Sufism, passed down from generation to generation. Furthermore, Sufism influenced the political world in Turkey and the period preceding the Ottoman Empire's collapse. Even after that, a new pattern of Sufism emerged, namely Sufism without order, which resulted from understanding the Risale-i Nur, written by Said Nursi.  Contribution: This article is expected to explain the role of Sufism in Turkey during the classical period as an agent of moderate Islam propagation who built a spirit of struggle. This study shows that Sufism in Turkey has different understandings from others that distance themselves from political matters, social activities, and state affairs.